Biodiversity and Nature Conservation Law and Policy in the Middle East and North Africa Region (Cambridge University Press, 2025)
This book will be useful to practitioners, policymakers, graduate students and researchers of environmental law, environmental studies, human rights, sustainable development, social justice and area studies on the Middle East and North Africa (MENA) and West Asia. This title is also available as open access on Cambridge Core.